1997
DOI: 10.1021/jp963892r
|View full text |Cite
|
Sign up to set email alerts
|

Rate Coefficients for the Reactions of Hydroxyl Radicals with Methane and Deuterated Methanes

Abstract: The rate coefficients for the reaction of OH with CH3D (k 1), CH2D2 (k 2), CHD3 (k 3), CD4 (k 4), and CH4 (k 5) as well as that of OD with CH4 (k 6) have been measured using the pulsed photolytic production of OH followed by its detection via pulsed laser induced fluorescence. k 1−k 4 and k 6 were measured between ∼220 and ∼415 K, while k 5 was measured down to 195 K. The measured rate coefficients do not strictly obey the Arrhenius expression. However, below 298 K, they can be represented by the expressions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
170
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(190 citation statements)
references
References 31 publications
(88 reference statements)
19
170
1
Order By: Relevance
“…The recent studies of Bott and Cohen (1989), Vaghjiani and Ravishankara (1991), Finlayson-Pitts et al (1992), Lancar et al (1992), Dunlop and Tully (1993), Mellouki et al (1994), Gierczak et al (1997) and Bonard et al (2002) are in good agreement, as shown by the Arrhenius plot in Fig. 1.…”
Section: Oh+methanesupporting
confidence: 70%
See 3 more Smart Citations
“…The recent studies of Bott and Cohen (1989), Vaghjiani and Ravishankara (1991), Finlayson-Pitts et al (1992), Lancar et al (1992), Dunlop and Tully (1993), Mellouki et al (1994), Gierczak et al (1997) and Bonard et al (2002) are in good agreement, as shown by the Arrhenius plot in Fig. 1.…”
Section: Oh+methanesupporting
confidence: 70%
“…However, over the temperature range ∼250-420 K the rate constants measured in these studies are significantly lower than most of the earlier absolute measurements (Atkinson, 1994). Gierczak et al (1997) fit their data and the earlier data of Vaghjiani and Ravishankara (1991) from the same laboratory to a three-parameter expression, and obtained the rate expression k(methane)=1.85×10 −20 T 2.82 e −987/T cm 3 molecule −1 s −1 . This rate expression is plotted as the solid line in the Arrhenius plot ( Fig.…”
Section: Oh+methanementioning
confidence: 62%
See 2 more Smart Citations
“…In the absence of a laboratory measurement for the ratio q, we resort to an estimate using analogous reactions. Recently Gierczak et al (1997) studied the abstraction reactions between OH and the deuterated isotopomers…”
Section: Enrichment Of Deuterium Through Methane Photochemistrymentioning
confidence: 99%